The phylogeny of the genus Nannochloropsis (Monodopsidaceae, Eustigmatophyceae), with descriptions of N. australis sp. nov. and Microchloropsis gen. nov - Fawley, M. W.; Jameson, I.; Fawley, K. P.
Strains of the genus Nannochloropsis (Eustigmatophyceae)from the Australian National Algae Culture Collection were evaluated by DNA sequence analysis. Strains were first assessed by sequence analysis of a 900-base-pair region of the plastid rbcL gene (bar-code analysis). This analysis allowed us to identify most of the strains at specific rank. However, the strains CS-416 and CS-759 produced a unique rbcL DNA sequence and were sister to N. oceanica in the phylogenetic analysis. Complete rbcL sequences and nuclear 18S ribosomal (r)DNA sequences were produced for these two strains. The results of phylogenetic analyses of an alignment of the concatenated 18S rDNA and rbcL sequences for Nannochloropsis taxa revealed that strains CS-416 and CS-759 represent a new species, N. australis. In addition, the analysis provided strong support for erecting a new genus, Microchloropsis, comprising the species M. salina and M. gaditana.
Keywords: DNA BAR CODE; EUSTIGMATOPHYCEAE; MICROCHLOROPSIS; NANNOCHLOROPSIS; RBCL; RDNA